Effects of Nutritional, Endocrine and Metabolic State on the Development of Intravascular Coagulation Induced by Human Serum Preparations with Procoagulant Activity - Antoniades, Harry N.; Iatridis, Panayotis G.; Westmoreland, Nelson; Simon, James D.; Hayes, Kenneth C.; Surgenor, Douglas MacN. (Thrombosis and Haemostasis, 1973)
Injection of human serum fractions with procoagulant activity into intact rats initiated hypercoagulability, thrombosis and hemorrhage. These in vivo effects were dependent upon the nutritional, endocrine and metabolic state of the animals. Injection in fed rats produced only transient hypercoagulability. In rats fasted 48 hours, the initial hypercoagulability was followed by prolonged hypocoagulation, a decline in blood platelet count, thrombosis and hemorrhage. These effects were reversed in fasted rats by glucose injected 1 hour before the serum fractions. Alloxan-diabetic fed rats and genetically obese fed rats also exhibited enhanced susceptibility to intravascular coagulation on injection of the serum fraction. However, injection of insulin in the diabetic rats before the serum fractions greatly reduced the susceptibility of these animals. The serum fractions used in these studies exhibited potent factor XIIa-like activity in vitro. The present studies demonstrate that the in vivo clotting process can be greatly influenced by the nutritional, endocrine, and metabolic state of the animal and they provide a basis for the investigation of the factors involved.